Purchase intentions towards international products among Bumiputera's consumers / Nor Faziela Fourzan - Fourzan, Nor Faziela (2018)
Globalization has become an inevitable circumstance that leads the entire worlds become one market which comprises of people from different backgrounds and cultures. It also provides various information and knowledge through the reductions of international barriers. As people around the world expose to variety windows of information with the help of Internet, their preferences and tastes keep on changing. This study is conducted to discuss and explore the factors that might influence purchase intentions towards international products among Bumiputera's consumers. A total of 150 surveys were distributed to individuals in Kota Samarahan, Sarawak. The factors identified are (a) advertisement; (b) brand image; (c) co untry-of-origin; and (d) perceived quality towards purchasing intentions of international products.